2021
DOI: 10.1177/1591019921990507
|View full text |Cite
|
Sign up to set email alerts
|

Flow diverter stents in the treatment of recanalized intracranial aneurysms

Abstract: Background We assessed the safety and efficacy of flow diverter stents (FDSs) in the treatment of recanalized or residual intracranial aneurysms treated endovascularly. Materials & Methods Patients whose recanalized or residual aneurysms were treated with FDSs in five tertiary hospitals were reviewed retrospectively. The patients’ demographic data, aneurysm characteristics, types of previous treatment, and clinical complications, or serious adverse events associated with FDSs, as well as the results of neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The safety and efficacy of PED implantation in a pre-existing stent remain unclear as data from different studies vary greatly. While previous studies indicated high recanalization rates with stent-assisted coiling, ranging from ∼57% to 78% (7,11), Park et al (12) reported a 94% complete closure rate of PED for recurrent aneurysms after stent-assisted coiling. Given the complexity of recurrent aneurysms after stentassisted coiling, these data suggest that PED may be the optimal alternative.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The safety and efficacy of PED implantation in a pre-existing stent remain unclear as data from different studies vary greatly. While previous studies indicated high recanalization rates with stent-assisted coiling, ranging from ∼57% to 78% (7,11), Park et al (12) reported a 94% complete closure rate of PED for recurrent aneurysms after stent-assisted coiling. Given the complexity of recurrent aneurysms after stentassisted coiling, these data suggest that PED may be the optimal alternative.…”
Section: Discussionmentioning
confidence: 95%
“…However, the safety and effectiveness of PED treatment for recurrent aneurysms after stent-assisted embolization have not been conclusively established (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…15 Several studies analyzed the use of flow diversion for recurrent or residual aneurysms with final complete obliteration results varying from 69% to 100%. 7,8,16,17 One such study by Daou et al 7 reported a complete aneurysm occlusion rate of 76.7% and near-complete aneurysm occlusion rate of 90% for a total rate of complete and near-complete aneurysm occlusion of 86.7% in 32 patients treated with FD for recurrent aneurysms after initial coiling. A similar study by Dornbos et al 8 evaluated 7 patients who underwent FD retreatment of previously coiled aneurysms with 80% complete occlusion at 6 months and 100% at 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…Longer devices with larger diameters were necessary for spanning of the fusiform segment, reliable opening, and improved apposition. Furthermore, rigorous platelet function testing and subsequent regimen adjustments were critical factors to mitigate neurologic complications from FD procedures ( 6 , 14 ). In our study, platelet function was assessed in 87.5% of procedures, and the rate of antiplatelet regimen adjustment was 21.4%.…”
Section: Discussionmentioning
confidence: 99%